Global public goods : international cooperation in the 21st century - Kaul, Inge; Grunberg, Isabelle; Stern, Marc A. (Oxford University Press, 1999)
"Globalization does not have to entail a loss of sovereignty. Indeed, if the proper policies are adopted, it can strengthen that sovereignty. But to manage globalization requires that we recognize the importance of global public goods. The essays here suggest innovative and practical strategies to ensure a more reliable supply of these public goods - such as environmental sustainability, market efficiency, equity, health, knowledge or peace." "The book's intent is to take the concept of global public goods out of the rarified circle of micro-economists and pass it as a practical tool into the hands of those who on a daily basis struggle with global policy challenges and crises." "Global Public Goods: International Cooperation in the 21st Century is for political leaders, offering concrete ideas on adjusting policymaking to the new realities. It is for students of economics and political science, proposing a definition of global public goods and exploring its applicability to a wide range of issues. It is for the development community, identifying innovative approaches to North-South cooperation. And it is for business and civil society, underscoring the need for a new tripartism in international policymaking."--Jacket